Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

clarkexo

  • 3 years ago

Remove the symbols of grouping (i.e., brackets, braces, parentheses)and collect terms: 3(x - y) + {5y - [3x - (2x - y)] + 4(x - y)}

  • This Question is Closed
  1. nickersia
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    = 3x-3y + (5y - (3x - 2x + y)) + 4x - 4y = =3x-3y + (5y - (x+y)) + 4x - 4y = =3x-3y + (5y - x - y) + 4x - 4y = =3x-3y + (4y - x) + 4x - 4y = =3x - 3y + 4y - x + 4x - 4y = =6x - 3y

  2. clarkexo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Would you be willing to help me with the others if I post them please?

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy